2015
DOI: 10.5120/20227-2511
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Job Scheduling Algorithms in Grid Computing

Abstract: Grid computing is a type of distributed computing that distributes the tasks to a group of network computers where computer are linked together to provide a better computational resource. Scheduling plays a vital role in gaining high consumption of resources in the field of grid computing and achieving utilization of resources in grid environments. The use of the scheduling is to increase the throughput, efficiency and decrease the average waiting time. In this paper we have been surveyed various job schedulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Experimental stages in this study: (1) Setting parameters whose values fixed and changes shown in table 1; (2) Setting the flexibility parameters and usability factors, are shown in table 2; (3) Generating jobs randomly with usability factors 2 and 3, and determining the percentage of flexibility from 25% to 100%, is shown in table 3. The results of the job generation in table 3 used as input to the FCFS-LRH, FCFS-EDS method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental stages in this study: (1) Setting parameters whose values fixed and changes shown in table 1; (2) Setting the flexibility parameters and usability factors, are shown in table 2; (3) Generating jobs randomly with usability factors 2 and 3, and determining the percentage of flexibility from 25% to 100%, is shown in table 3. The results of the job generation in table 3 used as input to the FCFS-LRH, FCFS-EDS method.…”
Section: Resultsmentioning
confidence: 99%
“…In general, a grid computing system is used to increase the utilization of homogeneous or heterogeneous resources so that workload management will be optimal [1][2][3] [4]. Computing resources facilitate organization formation such as servers, network nodes, storage elements [5].…”
Section: Introductionmentioning
confidence: 99%